(untitled) (Ozone Therapy Global Journal, 2017)
INTRODUCTION The OLEOZON® oral, is introduced in Stomatology in the 90 and in the therapies radical endodontic to principle of the 2000 receiving a notable impulse in order to establishing them definitively inside the therapeutic arsenal in the Primary Attention of Health. OBJECTIVE to evaluate the effectiveness of the OLEOZON® oral, like medication intraconducto in the treatment endodóntico of the municipality Beach. 2014. MATERIAL AND METHODS experimental Study, type rehearses historical control. The universe was conformed by 2644 patients that received treatments radical endodónticos concluded in the municipality Beach among January to December of the 2014 of any race and of both sexes, forming 2 groups of 400 patients each one chosen aleatorily, the control group, which received cures placing an sterile cotton absorbed in Cresophene to the entrance of the conduits, changing the cures every 48 hours. The study group received in the similar protocols the OLEOZON® oral. It was used as summary measures the absolute frequency and relative frequency and the test of comparison of stockings with a level of significance of 5% RESULTS The mostly represented ages were in the group from 19 to 59 years with 68,7% y 77,7%, in the group tried with OLEOZON® oral, the results they were a (94,4%) of cure in comparison with the group control (92,9%) after the second application. CONCLUSIONS So much the patient’s treaties with OLEOZON® oral, like with Cresophene they showed cure before the third application. In none of the patients treaties intolerance was reported the OLEOZON oral.